Wpływ publikacji wyników kwartalnych na cenę akcji : empiryczny test w warunkach polskiego rynku kapitałowego (2002-2005) - Sklinda, Sławomir; Kowalski,Tomasz (Earnings announcement impact on shareholders value : an empirical verification on the Polish market (2002-2005), 2006)
The aim of this paper is empirical verification of earnings (operating - 177 observations and net result - 228 observations) announcement impact on shareholders value. The null hypothesis of earnings announcement lack of impact on share’s abnormal return was tested applying both Brown and Warner [5] and Boehemer, Masumeci and Poulsen [3] techniques. Achieved results are coherent with expectations and surveys in other countries. Announcement of earnings higher than market consensus causes statistically significant positive abnormal returns (the strongest effect on the publication date), whereas information on worse that expected results in statistically significant negative abnormal results (the strongest effect on a day after publication).
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1133, s. 464-472